A Mechanosensory Receptor TMC Regulates Ovary Development in the Brown Planthopper Nilaparvata lugens - Jia, Ya-Long; Zhang, Yi-Jie; Guo, Di; Li, Chen-Yu; Ma, Jun-Yu; Gao, Cong-Fen; Wu, Shun-Fan (Frontiers in Genetics, 2020)
Transmembrane channel-like (TMC) genes encode a family of evolutionarily conserved membrane proteins. Mutations in the TMC1 and TMC2 cause deafness in humans and mice. However, their functions in insects are is still not well known. Here we cloned three tmc genes, Nltmc3, Nltmc5, and Nltmc7 from brown planthoppers. The predicted amino acid sequences showed high identity with other species homologs and have the characteristic eight or nine transmembrane domains and TMC domain architecture. We detected these three genes in all developmental stages and examined tissues. Interestingly, we found Nltmc3 was highly expressed in the female reproductive organ especially in the oviduct. RNAi-mediated silencing of Nltmc3 substantially decreased the egg-laying number and impaired ovary development. Our results indicate that Nltmc3 has an essential role in the ovary development of brown planthoppers.